Islamic FinTech and MSMEs: The Role of Religiosity and Product Knowledge - Majid, Rifaldi (Department of Islamic Economics, IPB University, 2024)
As the backbone of the national economy which is still struggling with the financing problem, prior studies on the intention to use Islamic FinTech for MSMEs are still rare. This study aims to examine whether both the religiosity (R) and product knowledge (PK) on Islamic FinTech products and services affect the intention to adopt it or not. A total of 100 responses were collected using an online questionnaire and then examined using structural equation modeling (SEM). The results show that subjective norm (SN), perceived usefulness (PU), as well as R, and PK significantly influence the intention to get financing and use the services offered. It is indicated that Indonesian MSMEs actors are getting aware and knowledgeable about sharia compliance of FinTech products. Likewise, the influence of social norms such as religious leaders and or the business environment also strengthens the intention. This means that there is a need for continuous efforts from the stakeholders by cooperating with sharia scholars in improving the Islamic financial literacy in order to eliminate the doubts on the practical side. This needs to be followed by strengthening consumer data protection as well as providing incentives in order to enlarge the industrial market share.